Spring sweet corn (Zea mays) response to irrigation levels, sowing methods and moisture conservation practices - Datta, Debarati; Chandra, Subhash; Chaturvedi, Sumit; Bhatnagar, Amit; Singh, Gurvinder; Singh, Veer (The Indian Journal of Agricultural Sciences, 2020)
A field experiment was conducted during spring (February-May) of 2017-18 at GBPUAT, Pantnagar to assess the effect of irrigation levels, sowing methods and moisture conservation practices on soil moisture, crop growth, productivity of spring season sweet corn. The experiment consisted of 3- irrigation levels including irrigation at IW/ CPE ratios of 1.0, 1.2, 1.4, 2- sowing methods (flat, furrow) and 3-moisture conservation practices (control, mulch @ 6 t/ha, biochar @ 3 t/ha) laid-out in a split-plot design, assigning combination of irrigation and sowing methods to main-plots and moisture conservation practices to sub-plots. The pooled results revealed that husked cob yield (15.79 t/ha) and biological yield (39.47 t/ha) of sweet corn were highest in IW/CPE 1.4 which were significantly higher than other two IW/CPE ratios. Furrow sowing resulted 8% increase in husked cob yield over flat sowing, while soil biochar application being at par with mulching showed significantly higher (6%) husked cob yield over control. The interaction effect showed that biological yield was at par between irrigation at IW/CPE 1.2 under furrow sowing and IW/CPE 1.4 under flat sowing. B: C ratio was higher with IW/CPE 1.4 (1.57), furrow sowing (1.54) and mulch (1.54). Higher soil moisture content before irrigation at tasseling stage was obtained under IW/CPE 1.4 (16.3%), furrow sowing (6.4%) and mulch (24.9%) as compared to IW/CPE 1.0, flat and control, respectively. Thus, sweet corn in sandy loam soil should be irrigated at IW/CPE 1.4, sown in furrows and supplemented with mulch or biochar application for enhancing productivity and profitability during spring season (February-May).